2016
DOI: 10.1213/ane.0000000000001160
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Monitoring Is Associated with Fewer Alarm Events During Planned Moderate Procedure-Related Sedation

Abstract: Supplemental Digital Content is available in the text.Published ahead of print February 1, 2016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
5
1
1
Order By: Relevance
“…This novel monitor detected airway obstruction before capnography and prolonged the time from detection of obstruction to desaturation. Patients who receive supplemental oxygen can have normal pulse oximetry signal even after the loss of P ETCO 2 due to obstructive apnea [11][12][13]. This is contrary to our results, however, and may be due to the short duration and low flow of supplementary oxygen which were inadequate to compensate hypoventilation in our patient population.…”
Section: Discussioncontrasting
confidence: 99%
“…This novel monitor detected airway obstruction before capnography and prolonged the time from detection of obstruction to desaturation. Patients who receive supplemental oxygen can have normal pulse oximetry signal even after the loss of P ETCO 2 due to obstructive apnea [11][12][13]. This is contrary to our results, however, and may be due to the short duration and low flow of supplementary oxygen which were inadequate to compensate hypoventilation in our patient population.…”
Section: Discussioncontrasting
confidence: 99%
“…The primary outcome was the incidence of decreased SpO 2 92% observed during the interval between the start of sedation and the end of the procedure. Although hypoxaemia is often defined as SpO 2 <90%, we chose, as other researchers did, 19,20,25,26 the 92% threshold considering that in patients breathing an FiO 2 of at least 0.50 (as planned per protocol), this would reflect clinically significant oxygenation impairment. SpO 2 and heart rate were recorded every minute during the procedure by the usual anaesthesia multiparameter monitor (Datex Ohmeda or Carescape B450 or Carescape B650; General Electric Healthcare, Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be explained by the use of an earlier version of PSI-calculating algorithm in these studies. Unfortunately, no recently published studies reported which PSI algorithm was used [18][19][20] with the exception of one [21,22]. In recently published studies, baseline PSI values were reported to range between 84 and 95, although data generally appear only in figures [19,23].…”
Section: Discussionmentioning
confidence: 99%